Through a relational lens: reflections about foster care experience in Italian emancipated foster youth - Cardinali, Paola; Bizzi, Fabiola; Migliorini, Laura (Frontiers in Psychology, 2023)
The study aimed to investigate relational outcomes of Italian emancipated foster youth across openended reflections about their perceptions of their relationships with the biological and foster family, with partner and peers. A total of 26 Italian emancipated foster youth (19-25 years old) recruited by social services completed a single in-depth interview. A qualitative thematic analysis was selected for this study. The results revealed two major themes of foster care experience that emerged often simultaneously from the participants' narration: 1) Positive Relational Outcomes including "Feeling supported", "Sense of belonging", "Good memories", "Relationship with family of choice", and "Staying in touch"; and 2) Negative Relational Outcomes referring "Devaluation", "Refuse", "Bad memories", and "Isolation". Foster care experience leads to complex relational perceptions in emerging adulthood according to different relational outcomes and ways of processing foster care experience. Professionals could work on relational outcomes and memories, especially during a critical transition like emerging adulthood, to support youth in making sense of their past experiences.Every year, many young people leave the foster care and protection system, approaching adulthood. Although there are several projects to support the transition to adulthood through gradual emancipation processes, it is important to promote a reflection on the experience of foster care at this stage of life to understand which processes can support processes of well-being and resilience among transition-aged foster youth (Richardson & Yates, 2014). In the process of foster care, a delicate balance of the affects is experienced and in this relational specificity it can be difficult to evaluate the outcome (Miller & Collins-Camargo, 2016). However, the study of the outcomes of foster care takes on a specific value for the young adult because this phase of transition towards autonomy is crucial for care leavers for the definition of their identity, of future projects and the fundamental choices in